PERSEPSI MASYARAKAT TERHADAP PANDEMI COVID-19 - Jubba, Hasse; Ferdaus, Nadia Nuril; Pratiwi, Winda Ika; Juhansar, Juhansar (DIALEKTIKA, 2021)
Since its appearance at the end of 2019, Covid-19 has become a big problem for all countries in the world. There are many perceptions that arise in the community regarding the origin of the emergence of the Covid-19 virus, both from a scientific and conspiracy perspective. Indonesia as a country with a Muslim-majority population, there are not a few perceptions that have emerged regarding this outbreak, even from some of them linking the emergence of the virus to religion. This paper aims to find out the public's perception of the current pandemic situation from a religious point of view and the entry of information from the media as well as policies that have been carried out by the government in the process of dealing with Covid-19. The method used is to use a survey essay as a substitute for interviews with limited access to distance (social distancing). The data obtained were analyzed using a qualitative descriptive approach. The results of this study show that most of the public's perceptions (54%) view the Covid-19 pandemic outbreak as a test, as much as 38% see it as a disaster, and as much as 2% see it as a curse, and the rest choose not to answer.Keywords: Perception, Muslim community, Covis-19, test, calamity, curse.